2006
DOI: 10.1002/pmic.200500595
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic approach to study the cytotoxicity of dioscin (saponin)

Abstract: Dioscin, extracted from the root of Polygonatum zanlanscianense pamp, exhibits cytotoxicity towards human myeloblast leukemia HL-60 cells. Proteomic analysis revealed that the expression of mitochondrial associated proteins was substantially altered in HL-60 cells corresponding to the dioscin treatment, suggesting that mitochondria are the major cellular target of dioscin. Mitochondrial functional studies validated that mitochondrial apoptotic pathway was initiated by dioscin treatment. Changes in proteome oth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
71
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 76 publications
(73 citation statements)
references
References 26 publications
2
71
0
Order By: Relevance
“…1A). Sarsasapogenin does not have the double bond at C 5 and C 6 and structurally resembles the aglycones of dioscin and polyphyllin D, which were previously reported to exhibit anticancer activities (1,2). TAIII was shown to suppress arachidonic acid-induced superoxide generation in human neutrophils (4) and increase the intracellular Ca 2+ concentration in endothelial cells (5).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1A). Sarsasapogenin does not have the double bond at C 5 and C 6 and structurally resembles the aglycones of dioscin and polyphyllin D, which were previously reported to exhibit anticancer activities (1,2). TAIII was shown to suppress arachidonic acid-induced superoxide generation in human neutrophils (4) and increase the intracellular Ca 2+ concentration in endothelial cells (5).…”
Section: Introductionmentioning
confidence: 99%
“…Evidence is accumulating to prove that saponins can inhibit tumor cell proliferation, with great potential to be developed as chemotherapeutic agents (1,2). Anemarrhena asphodeloides Bge.…”
Section: Introductionmentioning
confidence: 99%
“…0.5 mL Eppendorf tubes. The samples were digested following the protocol described by Wang Ying with some modifications (Wang et al, 2006). Briefly, the spots were washed twice with distilled water and destained with 15 mM potassium ferricyanide and 50 mM sodium thiosulfate and dehydrated in acetonitrile (ACN) followed by 25 mM ammonium bicarbonate.…”
Section: Two-dimensional Gel Electrophoresismentioning
confidence: 99%
“…Recent biological and pharmaceutical researches have shown that diosgenyl saponins may exert a large variety of biological functions, with a potential for use in cancer chemoprevention [88]. By using 2-DE, tryptic in-gel digestion and MALDI-TOF MS analysis, Wang et al [89] suggested that dioscin, a saponin extracted from Polygonatum zanlanscianense Pamp., exhibited cytotoxicity towards human myeloblast leukemia HL-60 cells. This proteomics analysis also revealed that the expression of mitochondria-associated proteins was substantially altered in HL-60 cells upon dioscin treatment, suggesting that mitochondria were the major cellular and organelle target of dioscin cytotoxicity.…”
Section: Application Of Proteomics For Research Into Traditional Herbmentioning
confidence: 99%